Migration of Salt Ions in Frozen Hydrate-Saturated Sediments: Temperature and Chemistry Constraints - Evgeny Chuvilin; Valentina Ekimova; Dinara Davletshina; Boris Bukhanov; Ekaterina Krivokhat; Vladimir Shilenkov (Geosciences, 2022)
Migration of dissolved salts from natural (cryopeg brines, seawater, etc.), or artificial sources can destabilize intrapermafrost gas hydrates. Salt transport patterns vary as a function of gas pressure, temperature, salinity, etc. The sensitivity of the salt migration and hydrate dissociation processes to ambient temperature and to the concentration and chemistry of saline solutions is investigated experimentally on frozen sand samples at a constant negative temperature (−6 °C). The experiments show that the ambient temperature and the solution chemistry control the critical salt concentration required for complete gas hydrate dissociation. Salt ions migrate faster from more saline solutions at higher temperatures, and the pore moisture can reach the critical salinity in a shorter time. The flux density and contents of different salt ions transported to the samples increase in the series Na2SO4–KCl–CaCl2–NaCl–MgCl2. A model is suggested to account for phase transitions of pore moisture in frozen hydrate-saturated sediments exposed to contact with concentrated saline solutions at pressures above and below the thermodynamic equilibrium, in stable and metastable conditions of gas hydrates, respectively.